(3Ydd GdCNHGQ GdJj QhjJ aj CMGOjK GdWgGQIs - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdj GdQGRj, CHh eMeO,J (B327 (3g` s ((3eMeO Hf CMeO Hf YHOGdgGOj GdebOSj s)
(3ChdgG (B:s
(3JHJOF HMOjK(B: (3Ef EeQCI cGfJ JgQGb GdOe, hcGfJ JMJ YHOGdQMef Hf Yha , Ke Ef QShd Gddg Udi Gddg Ydjg hSde CeQgG Cf JZJSd YfO cd UdGI hJUdj , cPG QhGg MSjf , hNCdag gTGe GdOThGFi aCQSdg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B87 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1440s
Keywords: (3GdMOjK h GdeUWdMs